A 2-Year Evaluation of Quality of Life Outcomes of Patients With Pelvic Organ Prolapse Treated With an Elevate Prolapse Repair System. Issue 6 (November 2016) - Buca, Danilo Italo Pio; Leombroni, Martina; Falò, Eleonora; Bruno, Matteo; Santarelli, Alessandro; Frondaroli, Franco; Liberati, Marco; Fanfani, Francesco
Abstract : Objectives: To evaluate 2-year quality of life of women with pelvic organ prolapse submitted to prosthetic correction with Elevate. Methods: We enrolled 116 consecutive patients with a stage ≥ to 2 prolapse. The Prolapse Quality of Life questionnaire was administered in the preoperative time and after 2 years of follow-up. The statistical results were obtained by using the SPSS Advanced Statistical™ 11.0 Software. Results: Patient's quality of life improved substantially following prosthetic vaginal surgery. In particular, a clear improvement in the "general state of patients health" ( P < 0.05), and a reduction in the daily physical, social, and psychological quality of life ( P < 0.05) connected to the prolapse of pelvic organ were observed. Furthermore, a significant reduction in the percentage of patients with urinal disturbances (86.2% preoperative vs 20.7% postoperative; P < 0.05), and an improvement in patient's relations with their partners with 12 patients resuming sexual activity were found. Conclusions: This study demonstrates that prosthetic vaginal correction represents a long-term efficient clinical instrument for women with symptomatic pelvic organ prolapse. It also achieves a resolution for urinary symptomatology and embarrassment, social limitation, physical and psychological difficulties of women, which, in great part, resulted in many overcoming surgical therapy, worried about fixed outcomes. Abstract : Single incision mesh surgery for treatment of POP results in improvement of QoL outcomes.